Employee Attendance Application Using QR Code Android-Based at Eria Hospital Pekanbaru - Krisbudiana, Muhammad Iqbal Fachry; Edi Susilo (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2023)
Eria Hospital has implemented a fingerprint attendance system, but it has some limitations such as difficulty in reading fingerprints, limited access to fingerprint scanner which is only located in one place, and dependence on shared equipment. To overcome these problems, an Android-based attendance application was developed using Waterfall software design. This application uses QR code and GPS to make it easier for employees to record their attendance while in the work area. The quality of this application is based on ISO 25010 quality standards, which include functional testing with all functionalities working well, reliability testing with an A rating, compatibility testing with split-screen feature compatibility, security testing with an A rating, portability testing with results can be install on different devices and Android versions 8.1 to 12, maintainability testing with an A rating, efficiency testing with a startup time of around 1.6 seconds, and user experience testing with attractiveness score of 2.62, perspicuity score of 2.57, efficiency score of 2.62, dependability score of 2.51, stimulation score of 2.62, and novelty score of 2.40. Overall, the implementation of an Android-based attendance application using QR Code has proved to be a viable solution to the challenges faced by the fingerprint attendance system, and has contributed to the optimization of attendance data collection and processing in Eria Hospital.